Advances in ion beam micromachining for complex 3D microfluidics - Ocola, Leonidas E.; Palacios, Edgar (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures, 2013)
In this paper, the authors present microfluidic mixers containing complex curvilinear and several tens of microns deep three-dimensional (3D) geometries used to decrease mixing lengths in passive microfluidic systems. In order to create these 3D geometries, the authors use ion beam micromachining (IBμM) and address redeposition and exposure strategy effects that follow this type of fabrication. Results of this work clearly demonstrate that fabrication of 3D microfluidic mixers using IBμM is achievable for real practical applications. In order to scale up to the tens of microns width and depth, and hundreds of microns in length fabrication, high current is required. This raises unique challenges of redeposition handling. This was achieved by realizing that redeposited silicon can be removed with an extended buffered oxide etch. In addition, data management and writing strategies not encountered in electron beam lithography have to be considered when designing the solid to be milled. Both designs, straight 3D and serpentine 3D mixers, were significantly faster mixers than the standard focusing mixer with no 3D texturing. This demonstrates that adding programmed depth variations to existing microfluidic devices can open new opportunities in microfluidic research and IBμM.